Public health nurses' caring behaviour can increase homecare patients' satisfaction - Syaharuddin; Yoga Tri Wijayanti; Mery Kana; Suprapto; Kens Napolion (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Background: Caring behaviour plays a vital role in the nursing profession, especially in public health settings. In-home care services, where patients receive medical attention in the comfort of their homes, the quality of care and patient satisfaction depend heavily on the nurse's ability to exhibit caring behavior. Objective: This study aims to analyze and identify the relationship between the caring behavior of public health nurses and the level of patient satisfaction in homecare services. Methods: In this study, the design used is a quantitative research design with a cross-sectional study approach. According to the formula found by Isaac and Micheal, the population in this study amounted to 402 respondents, so a sample of 162 respondents was obtained. The sampling technique was Probability Sampling with a proportional random sampling type. Results: Based on the results of the cross-tabulation that has been carried out between caring behaviour and patient satisfaction using the Fisher Exact test statistical test, the result is in the form of a p-value of 0.001 with a significant level of <0.05 and with this value (0.001) means less than the value a (0.05). It can indicate that Ha is accepted and Ho is rejected, and it can be concluded that caring behavior can increase patient satisfaction. Conclusion: Researchers suggest that the caring behavior of public health nurses has a vital role in increasing patient satisfaction with homecare services. Nurses can help patients feel more comfortable and supported in their home environment through more personalised attention, effective communication, and emotional support. This contributes directly to increased patient satisfaction, which feels valued and cared for holistically in-home care.